Increased Subfoveal Choroidal Thickness and Retinal Structure Changes on Optical Coherence Tomography in Pediatric Alport Syndrome Patients - Seda Karaca Adıyeke; Gamze Ture; Fatma Mutlubaş; Hasan Aytoğan; Onur Vural; Neslisah Kutlu Uzakgider; Gulsah Talay Dayangaç; Ekrem Talay (Journal of Ophthalmology)
Objective. To evaluate optical coherence tomography (OCT) findings of pediatric Alport syndrome (AS) patients with no retinal pathology on fundus examination. Materials and Methods. Twenty-one patients being followed up with the diagnosis of AS (Group 1) and 24 age- and sex-matched healthy volunteers (Group 2) were prospectively evaluated. All participants underwent standard ophthalmologic examination, retinal nerve fibre layer (RNFL) analysis, and horizontal and vertical scan macula enhanced depth imaging OCT (EDI-OCT). Statistical analysis of the data obtained in this study was performed with SPSS 15.0. Results. Macula thickness was significantly decreased in the temporal quadrant in Group 1 compared to those of the control group (p=0.013). RNFL measurements revealed statistically significant thinning in the temporal, superior, inferotemporal, and inferonasal quadrants and in average thicknesses in cases with AS compared to the controls (p<0.001, p<0.001, p=0.022, p=0.016, p<0.001, respectively). The mean subfoveal coronial thickness (SCT) was 362.2 ± 77.8 μm in Group 1 and 256,18 ± 71.7 μm in Group 2. There was a statistically significant difference between the two groups in terms of mean CT (p<0.001). Conclusion. OCT provides valuable information in identifying the structural changes and evaluation of ocular findings in patients with AS. Even if no pathological retinal findings were found in the clinical examination, structural changes in the OCT examination begin in early period of AS.